1989
DOI: 10.1111/j.1651-2227.1989.tb11130.x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in the Treatment of Metabolic Crises Caused by Inherited Disorders of Organic and Amino Acid Metabolism

Abstract: Four neonates who presented with coma secondary to hyperammonaemia resulting in central respiratory failure were treated with peritoneal dialysis for between 16 and 120 hours. Underlying diseases were maple-syrup-urine disease, propionic acidaemia and citrullinaemia in two patients. Clinical improvement was observed in three patients within 16 to 72 hours after institution of peritoneal dialysis. Biochemical analysis revealed a rapid reduction in plasma concentration of leucine, isoleucine and valine as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 20 publications
0
15
1
4
Order By: Relevance
“…The BCAA and a-ketoisocaproate blood levels obtained in our experimental model were close to those observed in neonates with MSUD when extracorporeal blood purification was required (Wendel et al 1980;Gortner et al 1989;Thompson et al 1991;Ring and Zobel 1992;Falk et al 1994). The epurative procedures were performed with a haemo(dia)filter and operational parameters already used in newborn infants.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The BCAA and a-ketoisocaproate blood levels obtained in our experimental model were close to those observed in neonates with MSUD when extracorporeal blood purification was required (Wendel et al 1980;Gortner et al 1989;Thompson et al 1991;Ring and Zobel 1992;Falk et al 1994). The epurative procedures were performed with a haemo(dia)filter and operational parameters already used in newborn infants.…”
Section: Discussionmentioning
confidence: 73%
“…The a-ketoisocaproate renal clearance is very low (Langenbeck et al 1979) and data about removal by peritoneal dialysis are scarce. Peritoneal clearance of a-ketoisocaproate in MSUD has been reported to be 0.62 ml/min in one neonate (Gortner et al 1989) and 1.1-1.9ml/min in an 18-month-old infant (Wendel et al 1980). The present study demonstrated that VVHDF gave higher a-ketoisocaproate clearances as compared with VVHE The a-ketoisocaproate clearances obtained with VVHDF at a 2L/h dialysate flow rate were 3.1 +0.7 and 5.0 + 1.2ml/min when Qb was 8.3 and 16.6 ml/min, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…However, peritoneal dialysis, at present, is not a preferred modality for the removal of ammonia because of slow rates of removal and unpredicted complications [21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…If it is the only available modality, it can be prescribed using 1.5% standard dextrose fluid, exchange volumes of 40-50 ml/kg, with hourly cycles for up to 36 h (to allow removal of most of the ammonia burden), or longer in UCD. Potential complications of PD include obstruction, leakage, infection, and mechanical failure [13,77,96].…”
Section: Dialysismentioning
confidence: 99%